Flavor Development for Functional Foods and Nutraceuticals. - Selvamuthukumaran, M.; Pathak, Yashwant (Nutraceuticals (Series), 2019)
In a finished nutraceutical product, flavors play an integral role. Flavor Development for Functional Foods and Nutraceuticals is about the crucial role added flavors play in any nutraceutical product. It describes the various extraction techniques that are being adopted for manufacturing flavors from natural raw materials. Yield and retention of aromatic components during several extraction methods and flavor encapsulation techniques for thermal degradable food components are discussed. Advanced methods of flavor extraction techniques like supercritical C02 extraction are emphasized. The safety and quality aspects of flavor incorporation in food processing industries are reviewed with respect to international regulations. The importance of flavor in the nutraceuticals industry is also discussed. In addition, the book stresses the functional value and organoleptic acceptability towards product optimization/formulation. Features: Explains how flavors play an integral role in a finished nutraceutical product Describes the various extraction techniques that are being adopted for manufacturing flavors from natural raw materials Covers flavor encapsulation techniques for thermal degradable food components Provides an introduction to the history of how some natural flavor ingredients, botanicals, and extracts were used in ancient times in Ayurveda and herbal medicine This is an ideal reference book for the flavor chemists, food scientists, nutraceutical formulators, and students and academicians who are working in the area of nutraceutical, supplement, and functional food development and provides very useful information to help them select appropriate flavors for their products. Also available in the Nutraceuticals: Basic Research/Clinical Applications Series: Flavors for Nutraceuticals and Functional Foods, edited by M. Selvamuthukumaran and Yashwant Pathak (ISBN: 978-1-1380-6417-1) Antioxidant Nutraceuticals: Preventive and Healthcare Applications, edited by Chuanhai Cao, Sarvadaman Pathak, Kiran Patil (ISBN 978-1-4987-3703-6) Food By-product Based Functional Food Powders, edited by zlem Tokuolu (ISBN 978-1-4822-2437-5).